Markers of Intestinal Damage and their Relation to Cytokine Levels in Cardiac Surgery Patients. Issue 6 (June 2017) - Habes, Quirine L.M.; Linssen, Vera; Nooijen, Suzan; Kiers, Dorien; Gerretsen, Jelle; Pickkers, Peter; Scheffer, Gert Jan; Kox, Matthijs
ABSTRACT: Objectives: In patients undergoing cardiac surgery, both extracorporeal circulation (ECC) and intraoperative mesenterial hypoperfusion may account for increased cytokine levels and lead to postoperative gastrointestinal (GI) symptoms. Methods: We investigated levels of the intestinal damage markers intestinal fatty acid binding protein (I-FABP in plasma [n = 72] and urine [n = 37]), citrulline (in plasma [n = 35]), and claudin-3 (in urine [n = 37]) in patients undergoing aortic or mitral valve surgery with or without coronary artery bypass grafting. Furthermore, the relationship between these markers and the surgery-induced cytokine response was explored by measuring serial plasma levels of tumor necrosis factor-α, interleukin (IL)-6, IL-8, and IL-10 (n = 35). Finally, the relationship between markers of intestinal damage and GI-symptoms (abdominal pain, ileus, vomiting, diarrhea, time to first defecation) was assessed. Results: Plasma and urinary I-FABP levels, and urinary claudin-3 levels peaked at the end of surgery, while citrulline levels were not influenced by surgery. ECC duration correlated with plasma I-FABP levels ( r  = 0.31, P  = 0.007). Plasma levels of all measured cytokines increased during surgery, with peak levels observed either at the end of surgery or on the first postoperative day. While ECC duration correlated with IL-6 and IL-8 release ( r  = 0.43, P  = 0.01 and r  = 0.36, P  = 0.04 respectively), there was no direct relationship between I-FABP and claudin-3 levels and cytokine concentrations. No patients developed significant GI or non-GI complications, and I-FABP and claudin-3 release appeared not to be related to postoperative GI symptoms, although the incidence of these symptoms may have limited a reliable assessment. Conclusions: Longer duration of ECC is associated with a more pronounced release of intestinal injury markers and inflammatory cytokines, but intestinal injury markers are not directly related to the observed increase in cytokine levels or GI-symptoms. These findings indicate that ECC duration contributes to the cytokine response observed in cardiac surgery patients and that intestinal injury itself is not a causative factor for this response.